2003
DOI: 10.1097/01.mp.0000056984.62360.6c
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Matrix Metalloproteinase 2 and Tissue Inhibitor of Metalloproteinase 2 Expression in Prostate Cancer

Abstract: Matrix metalloproteinases (MMPs) are proteolytic enzymes capable of degrading the structural support network for normal and malignant cells, promoting neoplastic cell invasion and metastasis. Tissue inhibitors of metalloproteinases (TIMPs) maintain connective tissue integrity by modulating MMP activity. Formalin-fixed paraffin-embedded tissue sections from 138 prostatic adenocarcinomas (PACs) were immunostained by a combined automated/manual method using monoclonal antibodies against MMP2 and TIMP2. Immunoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
3
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 51 publications
3
59
3
7
Order By: Relevance
“…In addition, TIMP-2 has been shown to promote cell growth (Hayakawa et al, 1994). Enhanced amounts of TIMP-2 protein are found to be associated with prostate cancer malignancies (Ross et al, 2003), but for colon and gastric cancer the correlation with clinico-pathological parameters has not been established (Ring et al, 1997;Joo et al, 2000). In our study, the CT/TT variant of TIMP-2 303C4T was observed more frequently in undifferentiated gastric carcinomas (WHO classification) and it was associated with worse tumour-related survival of gastric cancer patients.…”
Section: Discussioncontrasting
confidence: 49%
“…In addition, TIMP-2 has been shown to promote cell growth (Hayakawa et al, 1994). Enhanced amounts of TIMP-2 protein are found to be associated with prostate cancer malignancies (Ross et al, 2003), but for colon and gastric cancer the correlation with clinico-pathological parameters has not been established (Ring et al, 1997;Joo et al, 2000). In our study, the CT/TT variant of TIMP-2 303C4T was observed more frequently in undifferentiated gastric carcinomas (WHO classification) and it was associated with worse tumour-related survival of gastric cancer patients.…”
Section: Discussioncontrasting
confidence: 49%
“…26) However, unexpectedly, CPL did not exhibit the statistical significance, though CPL tended to inhibit the expression of MMP-2 and activate TIMP-2 by RT-PCR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, reasonable to postulate that this polymorphism may downregulate TIMP-2 expression and consequently cause an imbalance between the activities of TIMP-2 and MMP-2, which is believed to have a significant impact on cancer development and progression [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Of the four members in the TIMP family, TIMP-2 is particularly interesting because of its dual functions in terms of regulating MMP-2 activity [5] and its paradoxical effects on certain cancers [6,7]. A single nucleotide polymorphism (-418G/C) has also been identified in the promoter of the TIMP2 gene [8].…”
Section: Introductionmentioning
confidence: 99%